Acetyl-l-carnitine (ALCAR) for the prevention of chemotherapy-induced peripheral neuropathy in patients with relapsed or refractory multiple myeloma treated with bortezomib, doxorubicin and low-dose dexamethasone: a study from the Wisconsin Oncology Network - Callander, Natalie; Markovina, Stephanie; Eickhoff, Jens; Hutson, Paul; Campbell, Toby; Hematti, Peiman; Go, Ronald; Hegeman, Robert; Longo, Walter; Williams, Eliot; Asimakopoulos, Fotis; Miyamoto, Shigeki (Cancer chemotherapy and pharmacology, 2014)
Purpose Retreatment with bortezomib (B) is often considered for patients with relapsed multiple myeloma (MM), but this strategy is hindered by uncertainty of response and emergence of B-induced peripheral neuropathy (PN). We incorporated acetyl- l -carnitine (ALCAR) to prevent PN and allow for adequate dosing. We also investigated the correlation between B-inducible NF-κB activation and response to therapy. Methods Nineteen patients with relapsed/refractory MM received up to 8 cycles of intravenous bortezomib, doxorubicin and oral low-dose dexamethasone (BDD) to evaluate response and toxicity. Thirteen additional patients received prophylactic ALCAR (BDD-A). Patients receiving BDD-A were evaluated by FACT-GOG-TX, FACIT-Fatigue, Neuropathic Pain index (NPI) and Grooved Pegboard (GP) testing. Primary MM cells from 11 patients were tested for B-inducible NF-κB activation. Results Seventy-six percent of subjects were refractory to previous treatment, 39 % refractory to bortezomib. Median cycles received were 5. CR + PR for the entire group were 53 % and did not differ between groups. Incidence of ≥3 PN was 32 % in the BDD group versus 15 % in the BDD-A group ( p = ns). Patient-reported fatigue and PN measured by FACT-GOG-TX increased throughout the treatment period in the BDD-A group, although time to complete GP testing declined. In a sub-study examining constitutive bortezomib-inducible NF-κB activity in primary subject-specific MM cells, the presence of NF-κB activation correlated with lower likelihood of response. Conclusions Addition of ALCAR to BDD did not alter the incidence or severity of PN in relapsed MM patients receiving a B-based regimen. Bortezomib-inducible NF-κB activation in patient-derived primary MM cells may be associated with poorer response.